Response surface methodology on MHD stagnation-point flow of ternary hybrid nanofluid over a permeable radially shrinking disk - Yahaya, Rusya Iryanti; Mustafa, Mohd Shafie; Md Arifin, Norihan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Taylor and Francis, 2024)
The numerical and statistical investigations of Al2O3-TiO2-Cu/water ternary hybrid nanofluid in MHD stagnation-point flow over a permeable radially shrinking disk are conducted in the current study. Thermal radiation and convective boundary condition are also considered. The numerical investigation of the governing equations and boundary conditions is carried out using the bvp4c solver in Matlab. In this study, the wall shear stress produced by ternary hybrid nanofluid is 31.89% and 22.65% higher than the nanofluid and hybrid nanofluid, respectively. At the same time, the heat transfer rate of the ternary hybrid nanofluid is about 28.39% and 25.46% higher than the nanofluid and hybrid nanofluid, respectively. In addition, the increment of suction and magnetic parameters raises the local skin friction coefficient and Nusselt number. Meanwhile, the augmentation of the thermal radiation parameter and Biot number improves the temperature profile and local Nusselt number. With desirability of 99.75%, the local Nusselt number is maximized at 0.938137 when Rd=0.7, Bi=0.7, Ec=0.003, and M=0.5.